Analisis peran guru bimbingan dan konseling dalam pembentukan karakter siswa - Enggarto, Dhia Aliyah Aura Amani; Prasetyaningtyas, Wahyu Eka; Husain, Itsnain Alfajri (Universitas Indraprasta PGRI, 2024)
the purpose of the study was to determine the role of guidance and counseling teachers in shaping students' character at SMPN 91 Jakarta. The research method used in this study is a quantitative method with a survey approach. The data sources of this research are guidance and counseling teachers and IX grade students, a total of 68 students. The research instruments used are questionnaires, interviews, and observation and documentation. Observation is done by observing the environment and existence of the school. Data analysis techniques are carried out by grouping data according to similar student responses, namely very often, often, rarely, and never, then percentages are calculated and interpreted to draw conclusions as a result of the research. The results of the study concluded that